Transgender identity in young people and adults recorded in UK primary care electronic patient records: retrospective, dynamic, cohort study - Irene Petersen; Julia Bailey; Lorna Hobbs; Douglas Gordon John McKechnie; Elizabeth O'Nions; Frank Gillespie (BMJ Medicine)
Objectives To quantify the change in proportion of young people and adults identified as transgender in UK primary care records and to explore whether rates differ by age and socioeconomic deprivation.Design Retrospective, dynamic, cohort study.Setting IQVIA Medical Research Data, a database of electronic primary care records capturing data from 649 primary care practices in the UK between 1 January 2000 and 31 December 2018.Participants 7 064 829 individuals aged 10-99 years, in all four UK countries.Main outcome measures Diagnostic codes indicative of transgender identity were used. Sex assigned at birth was estimated by use of masculinising or feminising medication and procedural/diagnostic codes.Results 2462 (0.03%) individuals had a record code indicating a transgender identity. Direction of transition could be estimated for 1340 (54%) people, of which 923 were assigned male at birth, and 417 were assigned female at birth. Rates of recording in age groups diverged substantially after 2010. Rates of the first recording of codes were highest in ages 16-17 years (between 2010 and 2018: 24.51/100 000 person years (95% confidence interval 20.95 to 28.50)). Transgender codes were associated with deprivation: the rate of the first recording was 1.59 (95% confidence interval 1.31 to 1.92) in the most deprived group in comparison with the least deprived group. Additionally, the rate ratio of the proportion of people who identified as transgender was 2.45 (95% confidence interval 2.28 to 2.65) in the most deprived group compared with the least deprived group. Substantial increases were noted in newly recorded transgender codes over time in all age groups (1.45/100 000 person years in 2000 (95% confidence interval 0.96 to 2.10) to 7.81/100 000 person years in 2018 (6.57 to 9.22)). In 2018, the proportion of people with transgender identity codes was highest in the age groups 16-17 years (16.23 per 10 000 (95% confidence interval 12.60 to 20.57)) and 18-29 years (12.42 per 10 000 (11.06 to 13.90)).Conclusion The rate of transgender identity recorded in primary care records has increased fivefold from 2000 to 2018 and is highest in the 16-17 and 18-29 age groups. Transgender diagnostic coding is associated with socioeconomic deprivation and further work should investigate this association. Primary and specialist care should be commissioned accordingly to provide for the gender specific and general health needs of transgender people.